The Routledge Handbook of Catalysts for a Sustainable Circular Economy - Hanna Lehtimäki; Leena Aarikka-Stenroos; Ari Jokinen; Pekka Jokinen (Routledge, 2024)
This groundbreaking handbook leads the way in accelerating the transition to a sustainable circular economy by introducing the concept of a catalyst as a positive and enhancing driving force for sustainability. Catalysts create and maintain favourable conditions for complex systemic sustainability transition changes, and a discussion and understanding of catalysts is required to move from a linear economy to a sustainable and circular economy.With contributions from leading experts from around the globe, this volume presents theoretical insights, contextualised case studies, and participatory methodologies, which identify different catalysts, including technology, innovation, business models, management and organisation, regulation, sustainability policy, product design, and culture. The authors then show how these catalysts accelerate sustainability transitions. As a unique value to the reader, the book brings together public policy and private business perspectives to address the circular economy as a systemic change. Its theoretical and practical perspectives are coupled with real-world case studies from Finland, Italy, China, India, Nigeria, and others to provide tangible insights on catalysing the circular economy across organisational, hierarchical, and disciplinary boundaries.With its broad interdisciplinary and geographically diverse scope, this handbook will be a valuable tool for researchers, academics, and policy-makers in the fields of circular economy, sustainability transitions, environmental studies, business, and the social sciences more broadly.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.